A flea story : I want to stay here! : I want to go there! - Lionni, Leo, 1910- ([New York] : Pantheon Books, 1977)
Two fleas, one who loves to travel and one who prefers staying home, decide to go their separate ways.
Booklist
2.2
K-3
Keywords: Fleas -- Fiction; Fleas -- Fiction